New insights into Saccharomyces cerevisiae induced calcium carbonate precipitation - Li, Tianxiao; Zhang, Huabing; Tan, Xiang; Zhang, Rui; Wu, Fasi; Yu, Zongren; Su, Bomin (Frontiers in Bioengineering and Biotechnology, 2023)
Our previous study reported that Saccharomyces cerevisiae could induce calcium carbonate (CaCO3) precipitation, but the associated mechanism was unclear. In the present study, Saccharomyces cerevisiae was cultured under various conditions, including the presence of different organic acids and initial pH, and the yields of CaCO3 formation induced by the different organic acids were compared. The metabolism of organic acid by the metabolites of S. cerevisiae was also assessed in vitro. The SEM-EDS and XRD results showed that only acetate acid, pyruvic acid, and α-ketoglutaric acid could induce CaCO3 formation, and the weight order of the produced CaCO3 was pyruvic acid, acetate acid, α-ketoglutaric acid. In addition, the presence of only yeast metabolites and the initial neutral or alkaline environment also limited the CaCO3 formation. These results illustrated that organic acid oxidation intracellularly, especially the tricarboxylic acid cycle, was the major mechanism, and the CaCO3 yield was related to the amount of CO2 produced by the metabolism of organic acids. These findings will deepen the knowledge of the mineralization capacity of S. cerevisiae and provide a theoretical basis for the future application of yeast as an alternative microorganism in MICP.